FACTORS DEFINING POSITIONS OF LEFT PARTIES ON THE IMMIGRATION ISSUE - A. Z. Zinnatullin (Сравнительная политика)
In this article, we study factors defi ning left party’s policy positions on the immigration issue. This theme is not so popular in  political science despite of plenty of works devoted to that problem  in the context of far-right and mainstream parties. Therefore in this  paper, we propose our own models that takes into account two kinds of factors: endogenous (organizational) traits and exogenous (enviromental) arrangement. Proposed models try to explain the  position and saliency of immigration issue in the manifestos of  socialdemocratic, green and new left parties. We pay more attention  on several independent variables, such as electoral competition (we  operationalize it through the notion of effective number of parties  offered by Laakso and Taagepera), migration rate, popularity of far- right party, party’s nicheness, organizational traits (that we consider in terms of leaders-activists relations). We have two dependent  variables which called (1) party position on the immigration issue  and (2) saliency of this issue. In order to estimate necessary links  between variables we use regression analysis of time-series-cross- section data. As units of our research we present political party’s  moves in 10 Western European countries between 1975 and 2010.  We conclude that organizational peculiarities with its link to the  electoral competition make infl uence to the dependent variable.  Niche parties tend not to concentrate their attention on the issue of immigration, but if they do that greens and new lefts demonstrate proimmigrant positions. Social-democrats try to act less forthrightly  in order to maximize their electoral support.